COMPARISON OF NATURAL HEDGES FROM DIVERSIFICATION AND DERIVATIVE INSTRUMENTS AGAINST COMMODITY PRICE RISK: A CASE STUDY OF PT. ANEKA TAMBANG, TBK. - DWIPARANDI (NIM : 29111121) Pembimbing : Dr. Isrochmani Murtaqi, M.Acc., DIKDIK
Antam is a mining company in which most of its revenues come from the sales of diversified commodities, namely ferronickel (36.5% of total revenues in 2011), nickel ore (24.1%), gold (36.0%), silver (2.7%), and coal (0.8%). With the trend of declining nickel price in 2012, more than half of the company’s revenue is exposed to the nickel commodity price downside risk. Despite that, Antam claimed that its diversified commodities can reduce such impact, in other words it creates natural hedges, a hedging method that comes from daily activities. The topic of this final project is the commodity price risk of nickel against Antam’s natural hedge and other hedging tools. The focus of framework of research is on risk measurement, using Value-at-Risk (VaR), and risk mitigation, comparing VaR of portfolio and cost of hedging of derivatives. This research aims to find the strength of natural hedge compared to the use of derivatives to mitigate the risk of declining nickel price. Due to the limitation of data, only forward and option contracts are used as derivative instruments. The framework of research follows the Risk Loop, consisting of Risk Identification, Risk Measurement, Risk Mitigation and Risk Monitoring. The analysis starts with analyzing exposures, risk factors, and risk profiles, with the analysis of descriptive statistics to identify risk. Historical data is monthly commodity prices from February 2002 to December 2011 in Indonesian Rupiah (IDR). Forward and Option contracts are applied to ferronickel and nickel ore, which make four combinations of derivatives strategy. The time horizon for calculation of VaR and derivatives are 3 months, 6 months, and 12 months. Measurement of risk in natural hedge is conducted by calculating the VaR of portfolio using Delta-Normal approach. VaR at 99% confidence level then is compared to the company’s retained earnings in 2011. Comparison of natural hedge and derivatives is done by comparing VaR of natural hedge with the cost of hedging of derivatives strategy in three time horizon. Furthermore, more improved versions of the hedging techniques are considered. Since Antam’s diversified commodities are basically a portfolio, this portfolio is optimized using Markowitz mean-variances method to underline which commodities’ sales should be emphasized to minimize risk. The forward and option strategy is made more specific by applying both instruments in five different proportions to each nickel commodities, making 25 combinations of derivative strategy. Antam’s natural hedge is strong, as the VaR at 99% confidence level of 12 month is less than 10% of the company’s retained earnings in 2011. However, in short-term period, the costs of hedging of derivative instruments are smaller than the VaR of portfolio, so the use of forward and option to hedge the nickel commodities is recommended for the 3-month period. The recommended derivative strategy is to use put option in ferronickel and short forward in nickel ore. In implementation, Antam can use the analysis of forward and option fo